Subconscious Influence: A Clinical Experiment - Mouillot, Philippe (International Journal of Economic Practices and Theories, 2013)
Among the various influential techniques used by marketing professionals, subconscious suggestion probably ranks among the most dangerous ones, even if it is legal in many countries. But despite necessary ethical issues, which do not override other marketing technique’s legitimacy, the number of variables concerned is extremely large when observing and measuring subconscious impacts. We can then logically wonder if subliminal influence can really be anticipated and measured, as long as there are substantial reactions to be observed. This article presents two clinical experiments that have led to modify response behaviours up to 30%, and proposes the integration of the subliminal paradigm to the Engel, Kollat & Blackwell consumer behaviour model. Nevertheless, this experiment is clinical, consequently linked to a limited and controlled number of variables. It should then not be considered as a certainty in terms of subconscious consumer influence in real purchasing environments or situations.